Related Factors in Preparing for an Aging Society of Adults in Nakhon Si Thammarat - kimpu, wannisa; Noonil, Naiyana; Jantasuwan, Rachadaporn (Journal of The Royal Thai Army Nurses, 2023)
This descriptive cross-sectional study investigates variables associated with adults’ preparation to enter an aging society. The sample of adults aged 35-59 years, A total of 440 people. Data is collected through personal information, health behavior (3E 2S), knowledge and understanding of health (3E 2S) according to a standard questionnaire of the Division of Health Education, Ministry of Public Health. A questionnaire on attitudes toward the preparation to enter an aging society, social support, and the preparation to enter an aging society with a CVI value of 0.97. The reliability values were 0.95, 0.82, and 0.95, respectively, to indicate the reliability of the questionnaire. Frequency, percentage, mean, and standard deviation were all used in the data analysis. The Fisher’s or Chi-square test was used to examine the correlation. According to the study, there is a statistically significant correlation between their marital status, financial status, educational level, health behaviors (3E 2S), attitudes toward the preparation to enter an aging society, social support and the preparation to enter an aging society of adults (p<.01). Moreover, knowledge and understanding of health (3E 2S) significantly correlate with the preparation to enter an aging society of adults at p<.05.